Transcriptomic Profile of Tef (Eragrostis tef) in Response to Drought - Lorena Ramirez-Gonzales; Gina Cannarozzi; Abiel Rindisbacher; Lea Jäggi; Regula Schneider; Annett Weichert; Sonia Plaza-Wüthrich; Solomon Chanyalew; Kebebew Assefa; Zerihun Tadele (Plants)
The threat to world food security posed by drought is ever increasing. Tef [Eragrostis tef (Zucc.) Trotter] is an allotetraploid cereal crop that is a staple food for a large population in the Horn of Africa. While the grain of tef provides quality food for humans, its straw is the most palatable and nutritious feed for livestock. In addition, the tef plant is resilient to several biotic and abiotic stresses, especially to drought, making it an ideal candidate to study the molecular mechanisms conferring these properties. The transcriptome expression of tef leaf collected from plants grown under drought conditions was profiled using RNA-Seq and key genes were verified using RT-qPCR. This study revealed that tef exhibits a complex molecular network involving membrane receptors and transcription factors that regulate drought responses. We identified target genes related to hormones like ABA, auxin, and brassinosteroids and genes involved in antioxidant activity. The findings were compared to physiological measurements such as changes in stomatal conductance and contents of proline, chlorophyll and carotenoid. The insights gained from this work could play vital role in enhancing drought tolerance in other economically important cereals such as maize and rice.